EFFICACITE DE LA REGLEMENTATION PRUDENTIELLE DES BANQUES : VALIDATION EMPIRIQUE (Global Journal of Management and Business Research, 2016)
Abstract not found
Keywords: bank; capital; risk; prudential regulation